Varieties of consumer credit data regimes: A regulatory governance approach. Issue 1 (27th January 2020) - Mizrahi‐Borohovich, Inbar; Levi‐Faur, David
Abstract: Credit markets are expanding, and with them also the automated, large‐scale commercialization of personal credit data. The increasing use of data and scores for commodified decision making lends greater urgency to the study of credit data regulatory regimes. This article promotes a comparative regulatory governance perspective as the basis for theory‐driven, multidimensional measurement. In order to measure consumer protection, we distinguish three different subregimes (collection, profiling, and use) and construct a two‐dimensional index of consumer protection (market restriction and user empowerment). We then assess the index and demonstrate its applicability and validity, building on empirical analysis of the regulatory regimes in the United States, France, Sweden, and Israel for the year 2019. Our approach points to a new direction in researching and measuring regulatory regimes in a comparative manner, which looks beyond national analysis toward an in‐depth understanding of other, equally important, levels of variation.